2015
DOI: 10.1007/s00268-015-3111-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Management of Choledochal Cyst‐Technical Modifications and Outcome Analysis

Abstract: Laparoscopic excision of CDC is safe and feasible. Surgery should be performed early as outcomes are better in pediatric age as compared to adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 35 publications
2
28
1
4
Order By: Relevance
“…This results in more inflammation and fibrosis, which can result in a higher overall complication rate. 7 Indeed, a 2011 study by Cho et al that analyzed adult CDC patients reported a stricture rate of 6.3%, which is higher than stricture rates reported in the pediatric population. 15 Another factor that obviously needs to be considered is surgical expertise.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This results in more inflammation and fibrosis, which can result in a higher overall complication rate. 7 Indeed, a 2011 study by Cho et al that analyzed adult CDC patients reported a stricture rate of 6.3%, which is higher than stricture rates reported in the pediatric population. 15 Another factor that obviously needs to be considered is surgical expertise.…”
Section: Discussionmentioning
confidence: 89%
“…In fact, the average operation time of our study was about 160 minutes, which was shorter than the operation times reported previously, which was about 210*250 minutes. 7,14 But among the 4 patients included in our study, 1 patient developed anastomosis stricture. At routine follow-up, this patient showed an elevated total bilirubin level of 3.6 mg/dL and MRCP showed stricture at the HJ.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Методом выбора для большинства пациентов являются по возможности полное удаление кисты и гепатикоеюностомия на отключенной по Ру петле тонкой кишки [1,13,14].…”
unclassified
“…В мире описаны единичные наблюдения лапа-роскопических вмешательств при КЖП [2,9,[14][15][16]. Предлагаемое описание лапароскопического вмешательства по поводу КЖП основано на соб-ственном опыте.…”
unclassified